2013
DOI: 10.1179/1754762812y.0000000028
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implants in adults over 60: A study of communicative benefits and the impact on quality of life

Abstract: Cochlear implantation improves QoL of patients over 60 by the mere fact of having been implanted, regardless of poorer audiological benefits. Older patients, with long-term deafness experience a greater improvement in QoL after implantation. The results of this study should aid other centers when counseling patients on the expected, daily functional benefits of cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 11 publications
4
29
1
2
Order By: Relevance
“…Older patients experienced a higher subjective satisfaction after cochlear implantation, regardless of their CI audiometric benefit. Similar and consistent results had been previously observed by different studies in the past [8,[25][26][27][28] . Numerous large scale studies have demonstrated that several previous patient attributes condition cochlear implantation outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Older patients experienced a higher subjective satisfaction after cochlear implantation, regardless of their CI audiometric benefit. Similar and consistent results had been previously observed by different studies in the past [8,[25][26][27][28] . Numerous large scale studies have demonstrated that several previous patient attributes condition cochlear implantation outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…Accordingly to previous studies [6,8] , older patients obtained poorer results in terms of SR. Significant changes in QoL have been demonstrated in our sample according to GBI (Table 2, Figure 1) and SQ.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Two studies reported on disease-specific QoL instruments in adults, including the Specific Questionnaire (SQ) [Ramos et al, 2013], the NCIQ [Olze et al, 2012], and the Hearing Handicap Inventory -Adults (HHIA) [Vermeire et al, 2005]. The SQ evaluates 6 different aspects related [Faber and Grøntved, 2000;Ramos et al, 2013].…”
Section: Disease-specific Instruments In Older Adultsmentioning
confidence: 99%